Pengaruh Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Pegawai Pada Kantor DPRD Kota Bima - Muhamad Ardiansyah Pratama; Muhammad Badar (Journal of Management and Creative Business, 2023)
This research aims to determine the influence of the non-physical work environment on employee job satisfaction at the Bima City DPRD Office. This research is of associative type. The population used was 61 respondents using saturated sampling techniques so that the sample in this study was the entire population of 67 respondents. The research instrument used was a Likert scale questionnaire with data analysis techniques, validity test, reliability test, simple regression analysis, simple correlation analysis, determination test and significance test (T test). Based on the results of this research, it is concluded that the non-physical work environment has a significant effect on employee job satisfaction at the Bima City DPRD Office. This is proven by the T table value of 9.314 and sig 0.000. The determination test shows that job satisfaction is influenced by the non-physical work environment by 57.2%, while the remaining 42.8% is influenced by other factors or variables not included in this research.